2007
DOI: 10.1359/jbmr.070114
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor Genotype at Gln223Arg is Associated With Body Composition, BMD, and Vertebral Fracture in Postmenopausal Danish Women

Abstract: Leptin is emerging as a key regulator of bone remodeling. In a population-based study of 1306 postmenopausal Danish women, nonsynonymous LEPR SNPs were associated with risk of adiposity, BMD, and vertebral fracture. Smoking exacerbates this LEPR-associated fracture risk.Introduction: Nonsynonymous single nucleotide polymorphisms (SNPs) in the human LEPR gene have been associated with adiposity in a number of studies, but there have been no large-scale studies of their implications for BMD and osteoporotic frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 57 publications
3
16
1
1
Order By: Relevance
“…The results differ, with some studies finding an association with the substitution of adenine by guanine in position 668 of exon 6 (Gln223Arg) and changes in bone mass and an increase in vertebral fractures [11,12], but no modifications of bone density with the Lys656Asn polymorphism. These results are similar to those of our study.…”
Section: Discussioncontrasting
confidence: 58%
“…The results differ, with some studies finding an association with the substitution of adenine by guanine in position 668 of exon 6 (Gln223Arg) and changes in bone mass and an increase in vertebral fractures [11,12], but no modifications of bone density with the Lys656Asn polymorphism. These results are similar to those of our study.…”
Section: Discussioncontrasting
confidence: 58%
“…In literature, both alleles of these SNPs have been reported as risk alleles for type 2 diabetes and obesity, and a metaanalytic study reported nonsignificant associations. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]48 Consequently, additional studies in larger populations need to be carried out, to verify the involvement of these coding LEPR SNPs in the 'fetal insulin hypothesis'.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we therefore examined the effect of common SNPs in LEP and LEPR on birth weight and adult metabolic risk factors for type 2 diabetes measured in young twins recruited from the East Flanders Prospective Twin Survey (EFPTS). The SNPs studied have previously been associated with type 2 diabetesrelated traits in other populations, [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] and are either nonsynonymous or located in a region that might be of importance in the regulation of gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown recently in vivo, in animals and in humans, that glucocorticoidinduced osteoporosis has been linked to leptin production. 34,35 In view of the known properties of leptin on bone metabolism, it is tempting to speculate that corticosteroid exposure, leptin production and demineralization are linked events. Accordingly, the blockade of the leptin production would be favorable.…”
Section: Discussionmentioning
confidence: 99%